Influence of external heating rate on the structure and porosity of thermally exfoliated graphite oxide. (January 2017) - Qiu, Yang; Moore, Samuel; Hurt, Robert; Külaots, Indrek
Abstract: Fast external heating rates in graphite oxide thermal exfoliation have been reported to be advantageous for generating high surface area graphene-based materials for a variety of applications. The study yields the surprising result that the surface area and porosity developed in reduced graphite oxide under some conditions are independent of instrument-set external heating rates. The true "total" heating rate experienced by the sample is shown to be the sum of the external rate and the local self-heating rate associated with the exothermicity of graphite oxide exfoliation, and under many conditions, the local self-heating contribution dominates. In these instances, increasing external heating rate does not increase the total rate, improve exfoliation degree or enhance surface area. These results are important for optimizing the conditions for fabrication of reduced graphene oxide with tailored properties. Graphical abstract: